2013
DOI: 10.1080/13562517.2012.725221
|View full text |Cite
|
Sign up to set email alerts
|

The role of culturally responsive teaching for supporting ethnic diversity in British University Business Schools

Abstract: Diversity in British University Business SchoolsResearch into cultural differences in higher education is a growing phenomenon and there is a need to establish a theoretical framework that supports Business Schools in the personalisation of the pedagogical process. This paper investigates the role of Business School academics in shaping the pedagogical process that is culturally responsive to the unprecedented diversity in higher education. This paper attempts to uncover the pedagogical machinations that gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 14 publications
1
42
0
1
Order By: Relevance
“…Drivers of culturally responsive education are acknowledging, valuing, and using students' cultural backgrounds and cultural identities as conduits for building environments optimal for learning (Gay, 2010;Nieto, 1999). Research has demonstrated the positive benefits of strengthening connections between diverse communities to foster better teaching and enhance learning (Gurin, Day, Hurtado, & Gurin, 2002;Jabbar & Hardaker, 2013;Villegas & Lucas, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Drivers of culturally responsive education are acknowledging, valuing, and using students' cultural backgrounds and cultural identities as conduits for building environments optimal for learning (Gay, 2010;Nieto, 1999). Research has demonstrated the positive benefits of strengthening connections between diverse communities to foster better teaching and enhance learning (Gurin, Day, Hurtado, & Gurin, 2002;Jabbar & Hardaker, 2013;Villegas & Lucas, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Research (Jabbar and Hardaker 2013;Lumby and Foskett 2015) suggests that culture has the potential to create a student-teacher relationship which is fluid, built on high expectations and innovative classroom experiences. In this context, Piaget (1977) proposes that the onus is on the academic to create these experiences and to support ethnic minority integration into the classroom, helping and supporting them through the process of attaching meaning to new inputs and experiences based on their prior knowledge and beliefs.…”
Section: Theme 1: Culture As a Vehicle For Learningmentioning
confidence: 99%
“…This would go we argue some way in acknowledging the unique needs of ethnically diverse students (Beverly 2003;Rynes and Quinn Trank 1999), and acknowledge an increased awareness of the challenges of integration and adjustment in a technologically international environment. However, any such technological or pedagogical concepts need to be supported by multicultural policies and procedures and culturally relevant content (Jabbar and Hardaker 2013).…”
Section: The Use Of Moocs To Evolve From Isolated To Holistic Pedagogymentioning
confidence: 99%
See 2 more Smart Citations